Complement Dependent Synaptic Reorganisation During Critical Periods of Brain Development and Risk for Psychiatric Disorder - Westacott, Laura J.; Wilkinson, Lawrence S. (Frontiers in Neuroscience, 2022)
We now know that the immune system plays a major role in the complex processes underlying brain development throughout the lifespan, carrying out a number of important homeostatic functions under physiological conditions in the absence of pathological inflammation or infection. In particular, complement-mediated synaptic pruning during critical periods of early life may play a key role in shaping brain development and subsequent risk for psychopathology, including neurodevelopmental disorders such as schizophrenia and autism spectrum disorders. However, these disorders vary greatly in their onset, disease course, and prevalence amongst sexes suggesting complex interactions between the immune system, sex and the unique developmental trajectories of circuitries underlying different brain functions which are yet to be fully understood. Perturbations of homeostatic neuroimmune interactions during different critical periods in which regional circuits mature may have a plethora of long-term consequences for psychiatric phenotypes, but at present there is a gap in our understanding of how these mechanisms may impact on the structural and functional changes occurring in the brain at different developmental stages. In this article we will consider the latest developments in the field of complement mediated synaptic pruning where our understanding is beginning to move beyond the visual system where this process was first described, to brain areas and developmental periods of potential relevance to psychiatric disorders.